Chemoenzymatic synthesis of a novel N-2-hydroxyethyl)-beta-peptoid oligomer and application to porous polycaprolactone films - Monsalve, Leandro Nicolas; Petroselli, Gabriela; Erra Balsells, Rosa; Vazquez, Analia; Baldessari, Alicia (Polymer International)
Poly[N-(2-hydroxyethyl)-beta-propylamide] oligomer is syntehsized using a simple enzymatic procedure involving Candida antarctica lipase B. This novel compound is obtained by a green and chemoselective method from economic reactants in good yield. This beta-peptoid oligomer is characterized by spectroscopic methods showing low molecular weight and low dispersity. Two derivatives of this beta-peptoid oligomer ae prepared by acetylation and by grafting polycaprolactone by ring opening polymerization from the pendant hydroxyl groups. These products are blended with polycaprolactone to make films by solvent casting. The inclusion of the acyl derivatives of the beta-peptoid to polycaprolactone affects the morphology of the film yielding micro- and nanostructured patterns. Fil: Monsalve, Leandro Nicolas. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Oficina de Coordinacion Administrativa Houssay. Instituto de Tecnologia En Polimeros y Nanotecnologia; Argentina. Instituto Nacional de Tecnologia Industrial; Argentina Fil: Petroselli, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones En Hidratos de Carbono; Argentina Fil: Erra Balsells, Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones En Hidratos de Carbono; Argentina Fil: Vazquez, Analia. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Oficina de Coordinacion Administrativa Houssay. Instituto de Tecnologia En Polimeros y Nanotecnologia; Argentina Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos Aplicados A la Química Orgánica (i); Argentina